Use of ultrasonic diagnostics for investigation and detection of structural changes in the lungs in COVID-19 - Habchak, Andriy; Stasiv, Iryna (Journal of Education, Health and Sport, 2021)
Rapid and accurate diagnosis of various lung changes caused by SARS-Co V-2 is extremely important and relevant, as it will allow timely action to take the necessary measures to treat and stop the spread of lesions. Ultrasound diagnosis allows you to quickly, non-invasively, and cheaply conduct research that is accurate and effective enough to make or confirm a diagnosis. The article highlights the main structural changes in the lungs found in 86 patients with a positive PCR test for coronavirus virus. The following sonographic signs were observed during the study: B-line (in 54% of patients), white lung effect (in 20.6% of patients), consolidation (11 people – 17.5%), of which 6 patients with consolidation less than 1 cm and 5 patients had consolidations greater than 1 cm, pleural effusion was observed in 7 patients. Our research is important both in terms of increasing the informativeness of the diagnosis for physicians and patients, for whom it is important to quickly, non-invasively, and economically compare, detect disease and begin treatment promptly.